KONSEP KETELADANAN GURU DAN IMPLEMENTASINYA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Mohammad Saat Ibnu Waqfin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2019)
One of the most important and influential educational components is the teacher. Because the teacher is a central figure in improving the quality of education in students. Teachers in carrying out their duties are required to carry out various conditions, duties and responsibilities as instructors, educators and trainers. With a variety of demands that are so big and heavy, teachers in reality sometimes pay little attention to and implement these demands, so that they will influence and reduce the quality of education, especially students. The concept of teacher exemplary in terms of Islamic education is very important and is a very influential method in the process of formation and development of students. And this has been applied by the Apostle to his friends. As an educator, the teacher who becomes a character, role model and identification for students and their environment the teacher must implement the quality of his personality which includes authority, responsibility, independence, discipline, code of ethics, compassion, and mingling with society in daily life both in school environment and outside the school environment. Thus, the example of the teacher implemented in daily life will lead to the achievement of the goal of Islamic education to the fullest. From the explanation above, this is where the importance of this theme is about the example of the teacher in the perspective of scientific education to be studied by the author in the study of literature as a consideration or reference for educators, especially teachers.